Urinary Tract Infection due to Extended-Spectrum Beta-Lactamase Producing Organisms is a Risk Factor for Acute Kidney Injury among Patients with Type 2 Diabetes Mellitus - Rahim, Muhammad Abdur; Mitra, Palash; Haque, Ariful; Zaman, Shahana; Samad, Tabassum; Haque, Wasim Md Mohosin Ul; Ananna, Meheruba Alam; Chowdhury, Tufayel Ahmed; Saha, Shudhanshu Kumar; Sarker, Shyamal; et al. (Journal of Medicine, 2017)
Background: Urinary tract infection (UTI) is common and diabetic patients are at increased risk for UTI. UTI may be complicated by acute kidney injury (AKI). This study was designed to evaluate whether UTI due to extend ed-spectrum beta-lactamase (ESBL) producing organisms should be considered as a risk factor for AKI in type 2 diabetic subjects. Methods: This case-control study was done in a tertiary care hospital in Dhaka, Bangladesh from April to June 2016. Type 2 diabetic subjects with culture proven UTI were evaluated. Patients with UTI complicated by AKI were cases and those without AKI were taken as controls. ESBL-positivity of the isolated organisms was evaluated as risk factor for AKI. Results: During the study period, a total of 131 (male to female ratio 1:2.6) type 2 diabetic subjects with culture proven UTI were enrolled. Mean age and mean duration of diabetes were 56.1±13.3 and 8.7±5.4 years respectively. Escherichia coli (82, 62.6%) was the commonest aetiological agent followed by Klebsiella pneumoniae(14, 10.7%). Two-thirds (55/82, 67.1%) of E. coli and two-fifths (6/14, 42.9%) of Klebsiellae were ESBL-positive. UTI in 64 (48.9%) patients were due to ESBL-positive organisms. Out of 131 UTI patients, 62 (47.3%) had AKI; 40 (40/64, 62.5%) among ESBL-positive and 22 (22/67, 32.8%) among non-ESBL organisms. There were no significant difference in relation to age (p=0.71), sex (p=0.26), duration of diabetes (p=0.37) and glycated haemoglobin (HbA1c) (p=0.69) between cases and controls. ESBL-positivity appeared as a significant risk factor for AKI among the study subjects (OR=3.4, 95% CI=1.66-6.99, p=0.008). Conclusions: Almost half of the type 2 diabetic subjects with UTI had ESBL-positive organisms as aetiological agents in this study. UTI due to ESBL-positive organisms was a significant risk factor for AKI. J MEDICINE Jan 2018; 19 (1) : 40-43